The effect of SMS nudges on higher education performance - Alicia Brandt; Hamid R. Oskorouchi; Alfonso Sousa-Poza (Empirical Economics, 2023)
Driven by higher education's challenges in maintaining student motivation and achievement during the recent pandemic-induced shift to online learning, we investigate the effectiveness of text messages as a nudging tool to increase academic performance. To do so, we use a nonplacebo randomized controlled trial in which the treatment group directly receives SMS texts that review lecture content and give deadline reminders, while the control group only has access to the same information on the course page. Our findings suggest that the reception of motivating SMS messages per se, rather than the content review, has a positive effect on examination outcomes.
Keywords: I21; I23; 330; Nudging; Text messaging; Teaching